Women travelers: thinking online women’s networking for travel - Moraes, Camila; do Nascimento Silva, Beatriz Rosa (RITUR - Revista Iberoamericana de Turismo, 2021)
On Gender Studies, research on domestic violence, reproduction control rights, wage inequality, among others, are frequent, however, studies on women as tourists, that is, in their leisure time are still just few. When we relate gender studies to tourism, we end up addressing the issues of objectification of women, which may lead to the sexualization of the female body in studies on sex tourism or its constant association with domestic work in rural tourism. It is in this context that there is a need for studies and analysis on the use, right and access to free time by women and how this is associated with travel. In this sense, this article focuses on travel groups created on Facebook for women’s exclusivity and their exchange of information and creation of networks. For this, our theoretical framework was the new mobilities paradigm by Sheller and Urry (2006, 2016), more specifically the studies that characterize the gender mobilities and mobile justice (Sheller, 2008, 2018). Thus, it was concluded that such groups open space for new forms of contact and encounters, in addition to presenting themselves as a network of trust that enables the movements of women as tourists, as the groups help in understanding and recognition by women travelers of the frictions imposed on their movements as tourists.